PERLINDUNGAN HAK ANAK PASCA PERCERAIAN ORANG TUA - Esti Kurniati (Authentica, 2018)
Marriage after will give rise to legal consequences for both parties, not least the child of the marriage. The result is the emergence of rights and obligations. In fact, many households are unable to realize these goals and finally divorced, whereas marriage laws make every effort to reduce the number of divorces, as a result of divorce not only to parents but to children as well. Do not let children of divorce who have got the psychological burden, plus more for the rights of civilización the form of children's rights is not fulfilled by the parents. This paper has discussed the protection of children's rights after the divorce of both parents, which to answer is used legal research with a legislative approach and a conceptual approach. Legal protection for children both before and after divorce is needed to minimize the occurrence of things that are not desired by the child itself, such as the absence of affection, the child becomes neglected and the child also cannot get along as a child.Keywords: legal protection, divorce, and children's rights.